2018
DOI: 10.3889/oamjms.2018.490
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Side Effects in Non-Small Cell Lung Cancer Patients Treated With Combination of Chemotherapy and Conformal Radiotherapy

Abstract: BACKGROUND:Combined modality therapy is standard of care for patients with inoperable locally advanced non-small cell lung cancer (NSCLC), however, insufficient data exist regarding what chemoradiotherapy combination will be the gold standard.AIM:The study aimed to compare the survival impact and side effects of concurrent versus sequential radiochemotherapy treatment in inoperable stage III non-small cell lung cancer (NSCLC).METHODS:To evaluate the treatment results and prognostic variables, 85 NSCLC patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…The performance statuses of patients were evaluated using ECOG and KPS. In our study, similar to other studies, it was shown that there is a significant correlation between QLQ-C30 and QLQ-LC13 in patients with lung cancer to whom curative RT is administered [11][12][13]. A recent study showed that the relationship between KPS and QLQ-C30 was not significant [14].…”
Section: Discussionsupporting
confidence: 90%
“…The performance statuses of patients were evaluated using ECOG and KPS. In our study, similar to other studies, it was shown that there is a significant correlation between QLQ-C30 and QLQ-LC13 in patients with lung cancer to whom curative RT is administered [11][12][13]. A recent study showed that the relationship between KPS and QLQ-C30 was not significant [14].…”
Section: Discussionsupporting
confidence: 90%
“…Previous conclusions that weight loss was associated with worse prognosis were mostly derived from NSCLC patients received chemotherapy or concurrent chemo-radiotherapy 2 , 22 , 23 . It is unclearly why weight loss has a detrimental impact on survival for these advanced NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of weight loss as a prognostic indicator in the survival of patients with NSCLC is confirmed both in the univariate and multivariate analysis. Many researchers maintain that weight loss is associated with more aggressive disease (26)(27)(28). Specifically, Ross et al examined 418 NSCLC patients and found that those who lost weight completed less frequently three cycles of chemotherapy or their treatment was postponed more often.…”
Section: Discussionmentioning
confidence: 99%